Penyuluhan Pemanfaatan Transformasi Digital Bagi Organisasi Pemuda Batak Bersatu (PBB) - Azni Septiani, Noer; Hardiyan, Hardiyan; Wulansari Fridayanthie, Eka; Kusumaningrum, Aliffah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Digital transformation is not just about a technological development, but occurs at the intersection of people, business and technology guided by a broader business strategy. In every community organization there must be problems and obstacles that hit every organizational journey as well as the United Batak Youth Organization which still uses conventional media in every activity, by maximizing this digital transformation it can improve Human Resources in the United Batak Youth organization, especially in DPAC Cengkareng in every activity. The method of implementing community service uses a zoom meeting application between tutors and participants, because it is still in PPKM Level 3. Members of the United Batak Youth are given counseling on the use of existing digital as supporting activities. The results of this counseling will be made an article in electronic media as part of a report related to the implementation of community service activities for members of the United Batak Youth (PBB) DPAC Cengkareng. This research focuses on the use of digital transformation in the Batak united youth organization (PBB)